Influence of intraoperative vasopressor use on indocyanine green fluorescence angiography: first evaluation in an experimental model - Mahdi Al-Taher (Nature Portfolio, 2021)
Abstract Intraoperative indocyanine green (ICG) fluorescence angiography has gained popularity and acceptance in many surgical fields for the real-time assessment of tissue perfusion. Although vasopressors have the potential to preclude an accurate assessment of tissue perfusion, there is a lack of literature with regards to its effect on ICG fluorescence angiography. An experimental porcine model was used to expose the small bowel for quantitative tissue perfusion assessment. Three increasing doses of norepinephrine infusion (0.1, 0.5, and 1.0 µg/kg/min) were administered intravenously over a 25-min interval. Time-to-peak fluorescence intensity (TTP) was the primary outcome. Secondary outcomes included absolute fluorescence intensity and local capillary lactate (LCL) levels. Five large pigs (mean weight: 40.3 ± 4.24 kg) were included. There was no significant difference in mean TTP (in seconds) at baseline (4.23) as compared to the second (3.90), third (4.41), fourth (4.60), and fifth ICG assessment (5.99). As a result of ICG accumulation, the mean and the maximum absolute fluorescence intensity were significantly different as compared to the baseline assessment. There was no significant difference in LCL levels (in mmol/L) at baseline (0.74) as compared to the second (0.82), third (0.64), fourth (0.60), and fifth assessment (0.62). Increasing doses of norepinephrine infusion have no significant influence on bowel perfusion using ICG fluorescence angiography.